2014
DOI: 10.1007/s00531-014-1056-z
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and zircon ages of mafic dikes in the South Qinling, central China: evidence for late Neoproterozoic continental rifting in the northern Yangtze block

Abstract: of the supercontinent Rodinia, suggesting that continental rifting lasted until ca. 650 Ma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…Evidence of Neoproterozoic igneous activity is found in the Wudang and Yaolinghe Groups of the SQB and Neoproterozoic mafic plutons were also reported close to the Foping dome (e.g., Ling et al, 2002Ling et al, , 2007Zhu et al, 2008Zhu et al, , 2014b. The Neoproterozoic magmatic rocks have Mesoproterozoic Hf model ages (Ling et al, 2007(Ling et al, , 2010Zhu et al, 2009Zhu et al, , 2014aHu et al, 2016). Therefore, such rocks are potential source candidates for the migmatites.…”
Section: Zircon Grains From Group II Migmatites Preserve Both Triassimentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of Neoproterozoic igneous activity is found in the Wudang and Yaolinghe Groups of the SQB and Neoproterozoic mafic plutons were also reported close to the Foping dome (e.g., Ling et al, 2002Ling et al, , 2007Zhu et al, 2008Zhu et al, , 2014b. The Neoproterozoic magmatic rocks have Mesoproterozoic Hf model ages (Ling et al, 2007(Ling et al, , 2010Zhu et al, 2009Zhu et al, , 2014aHu et al, 2016). Therefore, such rocks are potential source candidates for the migmatites.…”
Section: Zircon Grains From Group II Migmatites Preserve Both Triassimentioning
confidence: 99%
“…It seems that igneous rocks of the Wudang and Yaolinghe Groups in the SQB also belong to this Neoproterozoic assemblage. They exhibit geochemical features of bimodal volcanism although their tectonic setting is still not yet well defined (Ling et al, 2002(Ling et al, , 2007Zhu et al, 2008Zhu et al, , 2014a.…”
Section: Zircon Grains From Group II Migmatites Preserve Both Triassimentioning
confidence: 99%
“…Our new CA‐ID‐IRMS ages of 637–641 Ma from the Yaolinghe Group represent the timing of major phases of volcanic activity around the Wudang rift zone. Previously, the Yaolinghe volcanic rocks were repeatedly dated using SIMS/LA‐ICP‐MS and produced controversial ages ranging from 685 ± 5 Ma to 636 ± 6 Ma (Deng et al., 2016; Ling et al., 2008; Zhu et al., 2015). Considering inheritance of zircon grains in mafic rocks and large analytical uncertainties, these previous SIMS/LA‐ICP‐MS radiometric ages are not accurate.…”
Section: Resultsmentioning
confidence: 99%
“…Recent zircon U‐Pb geochronology constrains the depositional ages of the Wudang and Yaolinghe groups in the range of 780–720 Ma and ca. 650–636 Ma, respectively (Cai et al., 2007; Deng et al., 2016; Ling et al., 2008; M. X. Wang, Wang, & Zhao, 2013; Zhu et al., 2014, 2015). Synchronous, cogenetic mafic‐ultramafic intrusions in the Wudang‐Suizhou‐Zaoyang areas represent the exposed plumbing system of the alkali volcanism in the Wudang area (L. J. Wang, Griffin, et al., 2013; M. Wang, Wang, & Sun, 2013; M. X. Wang, Wang, & Zhao, 2013; Wang et al., 2016; Xue et al., 2011; Zhu et al., 2015).…”
Section: Geological Setting and Samplingmentioning
confidence: 99%
“…Precambrian basement rocks are exposed in the Yudongzi Group, Foping area, Douling Group, Wuguan Group, Yaolinghe Group and Wudangshan Group in the SQB (Zhang et al 2001;Shi, Yu & Santosh, 2013). Of these, the Wudangshan Group is the most widely exposed basement strata in the SQB (Wang, R. R. et al 2016) and its formation has been dated at 830-726 Ma using U-Pb ages of zircons from volcanic interlayers and sedimentary rocks (Ling et al 2008(Ling et al , 2010, although some studies reported an age of 783-675 Ma (Xia et al 2008;, which is evidenced by the 632-688 Ma intruding plutons (Cai et al 2007;Ling et al 2008;Zhu et al 2015).…”
Section: A Geological Settingmentioning
confidence: 99%